Exploring restorative potential of biophilic servicescapes. Issue 4 (10th April 2018) - Purani, Keyoor; Kumar, Deepak S.
Abstract : Purpose: The purpose of this study is to explore the relationship between the biophilic stimuli present in the servicescape and restorative effects on psychological states among consumers. The research also examines moderating role of service contexts in this relationship. Design/methodology/approach: This empirical study applied a laboratory-like experimental design with one-shot treatment. About 566 usable responses were collected using six photographic images – three were biophilic environments and three were non-biophilic environments – for four a priori service contexts: hospital lobby, upscale restaurants, spa and bank lobby. Findings: The tests of hypotheses confirm restorative effects of biophilic servicescapes on consumer's psychological states, attention and mood, which, in turn, positively influence service preference. Further, the restorative effects of natural elements are found to vary across hedonic – utilitarian and experience – credence type service contexts. Originality/value: Because of higher levels of natural stressors, consumers today likely have attention fatigue and depleted mood states, which, in turn, may have adverse effects on their service consumption behaviour. In this context, building upon theories from environmental psychology, findings of this study contribute by establishing restorative potential of biophilic servicescape. The study also establishes that natural elements in biophilic servicescapes influence service preference, which is mediated by consumers' psychological states – attention and mood. Further, it demonstrates that consumers are more responsive with regards to such restorative effects of biophilic elements in contexts where they seek emotional, experiential value compared to rational, functional value.